1998
DOI: 10.1002/(sici)1098-2760(199803)17:4<231::aid-mop3>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Analytical derivation of a conformal perfectly matched absorber for electromagnetic waves

Abstract: We present an analytical deri¨ation of a 3-D conformal ( ) perfectly matched layer PML for mesh termination in general orthogo-nal cur¨ilinear coordinates. The deri¨ation is based on the analytic continuation to complex space of the normal coordinate to the mesh termination. The resultant fields in the complex space do not obey Maxwell's equations. Howe¨er, it is demonstrated that, through simple field transformations, a new set of fields can be introduced so that they obey Maxwell's equations for an anisotrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 14 publications
3
78
0
Order By: Relevance
“…In the series of papers [10][11][12], Teixeira and Chew showed that an appropriate change of field variables (analogous to Piola transforms for H(curl)-and H(div)-conforming fields) combined with complex coordinate stretching leads to Maxwellian PML for general curvilinear coordinates and anisotropic linear media. A similar approach was used for elastic wave propagation in [13,14], where the H(div)-conforming Piola transform was applied to the stress tensor.…”
mentioning
confidence: 99%
“…In the series of papers [10][11][12], Teixeira and Chew showed that an appropriate change of field variables (analogous to Piola transforms for H(curl)-and H(div)-conforming fields) combined with complex coordinate stretching leads to Maxwellian PML for general curvilinear coordinates and anisotropic linear media. A similar approach was used for elastic wave propagation in [13,14], where the H(div)-conforming Piola transform was applied to the stress tensor.…”
mentioning
confidence: 99%
“…The derivation of this metamaterial blueprint has close analogy with the derivation of Maxwellian perfectly matched layers (PMLs) for conformal boundaries [18]. This is because the latter can be derived in the various coordinate systems by applying a complex coordinate stretching (i.e., complexification on the metric of space) and the above metric invariance [10], [18].…”
Section: Hodge Operators and Masking Blueprintsmentioning
confidence: 99%
“…To truncate the computational domain, the wave port is filled with perfectly matched layers (PMLs) [20], which can be conveniently interpreted as a diagonal anisotropic medium. The PMLs are backed with perfectly electric conductor (PEC) or absorbing boundary conditions (ABCs).…”
Section: Formulationmentioning
confidence: 99%